Predictors of Emboli in Mechanical Thrombectomy for Anterior Circulation Stroke - Kwon, Yongho; Yi, Ho Jun; Shin, Dong-Seong; Kim, Bum-Tae (Current Neurovascular Research, 2024)
ObjectiveEmboli commonly occurs in mechanical thrombectomy (MT). The objective of this study was to analyze predicting factors of emboli after MT.MethodsPatients who underwent MT with successful reperfusion for anterior circulation occlusion were enrolled. Emboli included distal emboli at digital subtraction angiography (DSA) and unexpected embolic infarct on diffusion-weighted image (DWI) without distal emboli at DSA. Baseline characteristics, procedural details, angiographic outcomes, and clinical outcomes were reviewed. Multivariable analyses were performed to evaluate predictive factors for the occurrence of emboli.ResultsOf 601 patients, 149 (24.8%) patients had distal emboli at DSA, and 169 (28.1%) patients had unexpected embolic infarction on DWI even without distal emboli at DSA. A total of 318 (52.9%) patients were enrolled in the embolic group, and 283 (47.1%) patients were assigned to the non-embolic group. In multivariate analysis, larger microcatheter (OR 1.26, 95% CI 1.12–1.94; p = 0.047), clot passage (OR 1.33, 95% CI 1.07–1.87; p = 0.041), use of balloon guide catheter (BGC) (OR 0.70, 95% CI 0.52–0.92; p = 0.014), early ballooning of BGC (OR 0.68, 95% CI 0.50–0.90; p = 0.009), and longer stent retriever (OR 0.72, 95% CI 0.54–0.90; p = 0.029) were associated with occurrence of emboli.ConclusionMT with only a stent retriever, use of a larger microcatheter, and clot passage might increase the risk of emboli. In contrast, contact aspiration thrombectomy, use of BGC, early ballooning of BGC, and use of longer stent retrievers could reduce the chance of emboli.
Keywords: thrombectomy